Obsession in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel, 2014)
Eve has become the object of one person's obsession. Someone who finds her extraordinary, and thinks about her every hour of every day. Who believes the two of them have a special relationship. Who would kill for her, again and again. With a murderer reading meanings into her every move, handling this case will be delicate, and dangerous.